PENGEMBANGAN LKPD BERDIFERENSIASI SEBAGAI PENDUKUNG PEMBELAJARAN PENDIDIKAN AGAMA HINDU PADA KELAS VII SMP - Ni Kadek Ayu Desi Kernia; Putu Wulandari Tristananda; I Wayan Wira Darma (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
This development research aims to describe the design and construction, analyze the validity, and analyze the practicality of differentiated LKPD in the Hindu Religious Education subject for seventh-grade students at SMP Negeri 2 Singaraja. This research uses the Design and Development Research (DDR) method, which includes the stages of analysis, design, development, and evaluation. The research subjects involved material experts, media experts, language experts, teachers, and seventh-grade students from SMP Negeri 2 Singaraja. The analysis results show that students have diverse learning style characteristics, so a differentiated LKPD (Student Worksheet) was developed on the material of the form and function of offerings, which includes three types of learning activities: visual activities thru observation and image analysis, auditory activities through listening to audio and analyzing case studies, and kinesthetic activities thru simple practices. The results of the validity test show that the developed LKPD falls into the very valid categories with percentages of 95.83% in the material aspect, 82.5% in the media aspect, and 95% in the language aspect. Meanwhile, the practicality test results obtained percentages of 98.5% from teachers, 82% at the one-to-one stage, and 83.47% at the small group stage by students, all of which fall into the very practical category. Based on these results, the developed differentiated LKPD is deemed suitable for use as a meaningful and student-centered learning support. ABSTRAK Penelitian pengembangan ini bertujuan untuk mendeskripsikan rancang bangun, menganalisis validitas dan menganalisis kepraktisan LKPD berdiferensiasi pada mata pelajaran pendidikan Agama Hindu kelas VII SMP Negeri 2 Singaraja. Penelitian ini menggunakan metode Design and Development Research (DDR) yang mencakup tahapan analisis, perancangan, pengembangan, dan evaluasi. Subjek penelitian melibatkan ahli materi, ahli media, ahli bahasa, guru serta peserta didik kelas VII DMP Negeri 2 Singaraja. Hasil analisis menunjukkan bahwa peserta didik memiliki karakteristik gaya belajar yang beragam, sehingga dikembangkan LKPD berdiferensiasi pada materi bentuk dan fungsi upakara yang memuat tiga jenis aktivitas pembelajaran, yaitu aktivitas visual melalui pengamatan dan analisis gambar, aktivitas auditori melalui kegiatan menyimak audio dan menganalisis studi kasus, serta aktivitas kinestetik melalui praktik-praktik sederhana. Hasil uji validitas menunjukkan bahwa LKPD yang dikembangkan berada pada kategori sangat valid dengan persentase sebesar 95.83% pada aspek materi, 82.5% pada aspek media, dan 95% pada aspek bahasa. Sementara itu, hasil uji kepraktisan memperoleh persentase sebesar 98.5% dari guru, 82% pada tahap one to one, dan 83.47% pada tahap small group oleh peserta didik, yang seluruhnya termasuk kategori sangat praktis. Berdasarkan hasil tersebut, LKPD berdiferensiasi yang dikembangkan dinyatakan layak digunakan sebagai pendukung pembelajaran yang bermakna dan berpusat pada peserta didik.